2015
DOI: 10.1590/2359-3997000000013
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep and glycemic control in type 1 diabetes

Abstract: Objective: Our aim in the present study was to elucidate how type 1 diabetes mellitus (T1DM) and sleep parameters interact, which was rarely evaluated up to the moment. Materials and methods: Eighteen T1DM subjects without chronic complications, and 9 control subjects, matched for age and BMI, were studied. The following instruments used to evaluate sleep: the Epworth Sleepiness Scale, sleep diaries, actimeters, and polysomnography in a Sleep Lab. Glycemic control in T1DM individuals was evaluated through: A1C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 32 publications
2
55
3
1
Order By: Relevance
“…Similarly, Barone and colleagues showed that glycemic control modified the relationship between actimeter-measured sleep duration and glycemia in a small T1D study (n=18) [44]. Specifically, among individuals with T1D and HbA 1c <7%/53 mmol/mol, a strong negative correlation between glycemia and the night rest duration was observed (r= −0.90, p=0.04).…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Barone and colleagues showed that glycemic control modified the relationship between actimeter-measured sleep duration and glycemia in a small T1D study (n=18) [44]. Specifically, among individuals with T1D and HbA 1c <7%/53 mmol/mol, a strong negative correlation between glycemia and the night rest duration was observed (r= −0.90, p=0.04).…”
Section: Discussionmentioning
confidence: 88%
“…Hypoglycaemia, based on SMBG readings, was not related to sleep variables in this study (data not shown), which could be due to a limitation of SMBG in reflecting fluctuations in glucose levels typically seen in T1D. In addition, glycaemic variability was not assessed (by continuous glucose monitoring), although it was shown to be related to sleep impairment in one study (Barone et al ., ). When using the SD of SMBG values as an indicator of glycaemic variability, no associations with sleep variables were found (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…In these pilot studies, HbA1c was not clearly associated with the presence of sleep apnea; however, some data suggest that arousal index, assessed by polysomnography, could be linked to glycemic control (34). We therefore included an oximetric recording in the patients' sleep evaluation.…”
Section: Discussionmentioning
confidence: 99%